Do Good Corporate Governance, Whistleblowing System, and Modernization of the Administrative Tax System Affect Individual Taxpayer Compliance in Indonesia? - Puspitasari, Fitria; Surjandari, Dwi Asih (Neo Journal of economy and social humanities, 2023)
Taxes are the main source of revenue for the country. The level of taxpayer compliance is still fluctuating and inconsistent in Indonesia due to the distrust of taxpayers towards tax agencies and the lack of supervision over tax crimes and the complexity of the tax digitization system for most taxpayers, so that taxpayers are negligent and even ignore their obligations. This research aims to test the effect of good corporate governance, whistleblowing system, and modernization of the administrative tax system on taxpayer compliance. This is a quantitative research with the type of this research is primary, meaning that the researchers distributed the questionnaires to the respondents who are registered in Tangerang Tax Office, Indonesia. This research uses a non-probability sampling method with an accidential sampling technique to obtain the 100 samples. The results of this research show that good corporate governance and modernization of the tax administration system have a positive significant effect on taxpayer compliance, while the whistleblowing system has no effect on taxpayer compliance.